Multiple dwelling and tourism: negotiating place, home and identity - McIntyre, N.; McHugh, K. E.; McHugh, K. E.; McIntyre, N.; Williams, D. R.; Williams, D. R. (Wallingford :CABI, 2006)
This book focuses on migration or the movement and people and examines multiple dwelling as a societal response to the major influences of increased mobility and amenity tourism (visiting or residing in high-quality landscapes such as mountains, beaches and forests for leisure experiences). It considers the modern-day meaning of multiple dwelling, how it affects personal identity and the meaning of 'home', and its impacts on host communities and landscapes. This book will be of interest to those working in the areas of tourism, leisure, geography, outdoor recreation, sociology and anthropology. The book has 20 chapters, a subject index, and an author index.
Keywords: PP300 - Land Resources; UU100 - Housing and Settlement; UU200 - Demography; UU485 - Social Psychology and Social Anthropology, (New March 2000); UU600 - Leisure; UU700 - Tourism and Travel